THE CORRELATION BETWEEN STUDENTS’ VOCABULARY MASTERY AND READING COMPREHENSION AT THE SECOND GRADE OF SMA NEGERI 10 KOTA TERNATE - Abdullah, Surtila; Mukadar, Suraya (Four Son Scholarship, 2023)
This research is purposed to know the correlation between vocabulary mastery and reading comprehension at the second grade of SMA N 10 Kota Ternate. There are two variables in this research. Students vocabulary as independent variable (variable X) and Reading comprehension as dependent variable (Variable Y). The population of this research was all second grade of SMA N 10 Kota Ternate while the sample of the research were 30 respondents that taken from class 2 IPA1. This research used convenience sampling and applied quantitative descriptive with Pearson’s r correlation coefficient technique to analyze the data. The data were collected by using a test. The test consist of 30 items of vocabulary mastery test and 30 items of reading comprehension. The result of the research found that there is a significant correlation between vocabulary mastery and reading comprehension is 31.77. While in Pearson’s r table with the degree of significance 5% is 0.367. It means that correlation coefficient of 31.77 is significant and the null hypothesis is rejected because rxy>rt = 31.77>0.367. In other words, the alternative hypothesis that stated there is significant correlation between vocabulary mastery and reading comprehension is accepted. the suggestion of this research is that in developing the vocabulary mastery and reading comprehension teacher should encourage the students to have and use dictionary as a tool to help them with difficult words and the teacher should support the students expectation about reading and arouse their interest to increase their reading comprehension.